Isolation, Screening, and Identification of Actinomycetes with Antifungal and Enzyme Activity Assays against Colletotrichum dematium of Sarcandra glabra. Issue 1 (2nd January 2020) - Song, Lisha; Jiang, Ni; Wei, Shugen; Lan, Zuzai; Pan, Limei
Abstract: A serious leaf disease caused by Colletotrichum dematium was found during the cultivation of Sarcandra glabra in Jingxi, Rong'an, and Donglan Counties in Guangxi Province, which inflicted huge losses to plant productivity. Biological control gradually became an effective control method for plant pathogens. Many studies showed that the application of actinomycetes in biological control has been effective. Therefore, it may be of great significance to study the application of actinomycetes on controlling the diseases caused by S. glabra . Strains of antifungal actinomycetes capable of inhibiting C. dematium were identified, isolated and screened from healthy plants tissues and the rhizospheres in soils containing S. glabra . In this study, 15 actinomycetes strains were isolated and among these, strains JT-2F, DT-3F, and JJ-3F, appeared to show antagonistic effects against anthracnose of S. glabra . The strains JT-2F and DT-3F were isolated from soil, while JJ-3F was isolated from plant stems. The antagonism rate of strain JT-2F was 86.75%, which was the highest value among the three strains. Additionally, the JT-2F strain also had the strongest antagonistic activity when the antagonistic activities were tested against seven plant pathogens. Strain JT-2F is able to produce proteases and cellulase to degrade the protein and cellulose components of cell walls of C. dematium, respectively. This results in mycelia damage which leads to inhibition of the growth of C. dematium . Strain JT-2F was identified as Streptomyces tsukiyonensis based on morphological traits and 16S rDNA sequence analysis.